Main Player in Industrial Carbon Emissions in China - Liu Zhenling (Institute of Advanced Engineering and Science, 2013)
The carbon emissionshas attracts great concerns in engineering technology researches. The decomposition analysis technology has been popular in the study on influencing factors of industrial carbon emissions(ICE). The change of industries’s CO2 emissions from the three main industries in China over the period 1980-2011 based on the logarithmic mean divisia index (LMDI) method has been carried out. The research indicated that economic activity effect was the main influence factor for ICE increase in China over the entire period; the decline in energy intensity and the adjustment of energy and change in the CO2 emission coefficient were major determinants for reduction of ICE. Meanwhile, we found that China had made a significant contribution to reducing global CO2 emissions by decreasing its energy intensity. Based on the fore study, the mechanism of CO2 emission changes has been analyzed and the pressure-driven environment protection model has been put forward. http://dx.doi.org/10.11591/telkomnika.v11i5.2484